2019
DOI: 10.1158/2326-6066.cir-18-0145
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA-MM2P Identified as a Modulator of Macrophage M2 Polarization

Abstract: M2 polarization of macrophages is essential for their function in immunologic tolerance, which might promote tumorigenesis. However, the molecular mechanism behind the polarization process is not fully understood. Given that several lines of evidence have suggested that long noncoding RNAs (lncRNAs) could be involved in regulating immune cell differentiation and function, the current study aimed to identify the lncRNAs that specifically modulate M2 macrophage polarization. By utilizing a series of cellbased M2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 44 publications
2
97
0
Order By: Relevance
“…Thus, lincRNA-Cox2 may act as a suppressor of M2-polarization of macrophages to inhibit immune evasion and growth of tumor cells (66). Contrastingly, lncRNA-MM2P was reported to be involved in M2-polarization and M2 macrophage-mediated angiogenesis, which may have a potential role in macrophage-mediated tumorigenesis (76). Other lncRNAs, such as MIR155HG and CCAT1 have also been recognized as regulators of macrophage polarization (79,103).…”
Section: Tamsmentioning
confidence: 99%
“…Thus, lincRNA-Cox2 may act as a suppressor of M2-polarization of macrophages to inhibit immune evasion and growth of tumor cells (66). Contrastingly, lncRNA-MM2P was reported to be involved in M2-polarization and M2 macrophage-mediated angiogenesis, which may have a potential role in macrophage-mediated tumorigenesis (76). Other lncRNAs, such as MIR155HG and CCAT1 have also been recognized as regulators of macrophage polarization (79,103).…”
Section: Tamsmentioning
confidence: 99%
“…For example, lncRNA GAS5 was significantly reduced in M2-polarized microglia, and overexpression of GAS5 suppressed microglial M2 polarization via inhibition of transcription of IRF4, which is an important regulatory molecule of M2 polarization [44]. As we discussed, lncRNA MM2P was higher expressed in M2 macrophages rather than in M1 macrophages, and blockade of lncRNA MM2P could weaken the IL-4/STAT6 signaling pathway, resulting in a reduction of both cytokine-regulated M2 polarization and M2-induced angiogenesis [32]. NF-κB, which is a downstream signaling pathway of toll-like receptors (TLRs) after specific microbial and pathogen recognition, could induce transcription of proinflammatory genes and is strongly involved in the regulation of macrophage polarization [45].…”
Section: Lncrnas Regulate Macrophage Infiltration Polarization and mentioning
confidence: 72%
“…LncRNAs could also induce macrophage polarization and lead to regulatory effects on their functions. Lipopolysaccharide (LPS) and interleukin-(IL-) 4 induction was commonly applied for M1/M2 macrophage polarization, respectively [32]. Ye et al observed that lncRNA Cox-2 is expressed higher in LPS-induced M1 macrophages than IL-4-induced M2 macrophages, and silencing lncRNA Cox-2 expression markedly altered the macrophage polarization from M1 to M2 phenotype [40].…”
Section: Lncrnas Regulate Macrophage Infiltration Polarization and mentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of lncRNA-MM2P in RAW264.7 could cut down the M2 polarization by decreasing phosphorylation level of STAT6. 86 LncRNA growth-arrest-specific transcript 5 (GAS5) was up-regulated in human monocyte-derived macrophages from pneumonia children and acted as a miR-455-5p decoy to up-regulate SOCS3, then inhibited JAK2/STAT3 signalling and increased the transformation of M1 macrophage 87 ( Figure 2 and Table 1).…”
Section: Characteristics Of Lncrnas In M2-like Macrophage M1/m2 Swmentioning
confidence: 99%